2007
DOI: 10.1037/0096-1523.33.1.137
|View full text |Cite
|
Sign up to set email alerts
|

The suppression of reflexive visual and auditory orienting when attention is otherwise engaged.

Abstract: Two experiments were conducted to examine whether abrupt onsets are capable of reflexively capturing attention when they occur outside the current focus of spatial attention, as would be expected if exogenous orienting operates in a truly automatic fashion. The authors established a highly focused attentional state by means of the central presentation of a stream of visual or auditory characters, which participants sometimes had to monitor. No intramodal reflexive cuing effects were observed in either audition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
99
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(110 citation statements)
references
References 72 publications
8
99
3
Order By: Relevance
“…Note that onsets do indeed appear to satisfy the resistance-to-suppression criterion (Christ & Abrams, 2006). Our findings are consistent with previous results that showed that involuntary orienting caused by onsets was impaired by a concurrent dual task (Boot et al, 2005;Santangelo et al, 2007). In addition, the fact that the exogenous cuing effect only suffered at short target-probe lags (lag 2 in Experiment 1 and lags 2 and 3 in Experiment 2) and recovered at longer lags further indicates that involuntary orienting was sensitive to the manipulation of available attentional resources (attentional resources recover as target-probe lag increases).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Note that onsets do indeed appear to satisfy the resistance-to-suppression criterion (Christ & Abrams, 2006). Our findings are consistent with previous results that showed that involuntary orienting caused by onsets was impaired by a concurrent dual task (Boot et al, 2005;Santangelo et al, 2007). In addition, the fact that the exogenous cuing effect only suffered at short target-probe lags (lag 2 in Experiment 1 and lags 2 and 3 in Experiment 2) and recovered at longer lags further indicates that involuntary orienting was sensitive to the manipulation of available attentional resources (attentional resources recover as target-probe lag increases).…”
Section: Discussionsupporting
confidence: 82%
“…There is clearly a discrepancy between the results of Ghorashi et al (2007) on one hand and Boot et al (2005) and Santangelo et al (2007) on the other. How can we reconcile the discrepancy?…”
contrasting
confidence: 51%
See 1 more Smart Citation
“…Error bars 95% within-subjects confidence intervals calculated as per Masson and Loftus (2003) there is evidence for a neuroanatomical overlap between areas involved in object processing during the AB, and exogenous orienting. Moreover, a number of studies have shown conditions under which attentional capture by exogenous cues is attenuated (e.g., Santangelo, Olivetti Belardinelli, & Spence, 2007;Theeuwes, 1991;Yantis & Jonides, 1990;see Santangelo & Spence, 2008 for a review). Together, this evidence suggests that processing of exogenous cues may be impacted by intention and concurrent task performance, consistent with the effects of object processing obtained in the current experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, if the difficulty of a single task increases (high load), it could be expected that simultaneous performance of a second task (tone detection) should decrease, as greater cognitive control would be required to perform both tasks simultaneously. Santangelo, Olivetti Belardinelli, and Spence (2007), for example, demonstrated that under the highly focused attentional state required for monitoring a stream of centrally presented visual stimuli consisting of letters and numbers (a high-perceptual-load task), the performance of an orthogonal cuing task involving determining the spatial location of an auditory stimulus was diminished or eliminated. Similar effects have been found for the addition of a second attention-demanding task across other modalities (see , for a review).…”
Section: Attention and Processing Task-related Stimulimentioning
confidence: 99%